INDICADORES ANTROPOMÉTRICOS DE OBESIDADE: ASSOCIAÇÃO COM HIPERTENSÃO E GORDURA VISCERAL. - CALADO, Isabela Leal (2016)
The prevalence of obesity has increased dramatically in developed and emerging countries. Simultaneously, it is observed the increase in the prevalence of diseases such as hypertension. In the black population, obesity is a chronic problem, and the prevalence of hypertension is twice as high as in whites. It is agreed that the risk for cardiovascular diseases are associated more to central obesity, than to total obesity. Computed tomography (CT) is the gold standard for assessment of body composition, but its high cost limits the use in clinical practice and in epidemiological studies. Anthropometric indicators of obesity (AIO) are alternatives for their safety, ease and correlation with visceral fat. However, the literature differs on what would be the best method to be used for this purpose. This study had two goals: to investigate association between AIO and hypertension in African descent and determine the AIO which shows greater relationship with visceral adipose tissue (VAT) in hypertensive African descent residing in Quilombo communities in Alcantara-MA. In the first article we evaluated 932 African descent aged <60 years, using the variables: blood pressure, body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR), waist-to-height (WHtR), conicity index (C Index) and sagittal abdominal diameter (SAD). To evaluate the association between hypertension and AIO it was used the Poisson regression model with robust variance. The results showed that BMI was associated with hypertension in both sexes, but the AIO that remained as a risk factor for hypertension, was DAS for men and WC and WHtR for women. In the second article, we evaluated 143 hypertensive African descent aged ≥ 18 years. The following AIO were used: BMI, WC, WHR, WHtR and SAD. The TAV was evaluated by TC, for single volumetric cut at the level of L4-L5 vertebrae. To assess the relationship of the AIO with VAT, we used multiple linear regression analysis, initially adjusted for age and later by age, weight, height and hip circumference. BMI, WHtR and WHR were not included due to collinearity with the weight, height and hip circumference. The results showed that in men, 2 CC showed higher relationship with TAV (Coef = 7.37; p value <0.0001; R = 57.0%). For women, DAS was the AIO that was most associated with TAV (Coef = 0.60; p value <0.023; 2 R = 54.0%). This study concluded that BMI can be used as an anthropometric index of obesity to assess the risk of hypertension in African descent living in quilombola communities. Already in hypertensive African descent, WC was the AIO that was better related to the VAT in men, while the SAD with the VAT of hypertensive women.